Os conhecimentos prévios e o ensino de números inteiros - Soares, Luís Havelange (2007)
This research study consists of seeking and analyzing the predominant conceptions among mathematics teachers about previous knowledge and its use in the classroom. Integer Number Set was the theme worked; being the research subjects four (4) six grade (12 years old) mathematics teachers of the Fundamental Level at a public school of the State of Paraíba. Questionnaires, interviews and classroom observations were used for the data collection. The Ausubel´s theory of (ver em ingles neste caso..) learning was used for discussing the process of teaching and learning Mathematics. Mandarino´s categorization was adopted to analyze the teaching conceptions. Mandarino (2006) classifies the teaching conceptions in the teaching of Mathematics as formal or traditional conception, utilitarian or instrumental conception and relational conception. It has been noticed, in the day by day teacher´s practice on the teaching of integer numbers that three (3) of the four teachers act on the utilitarian or instrumental conception and one (1) of them on the relational conception. The three teachers reduce the previous necessary knowledge for approaching integer numbers to the four operations to natural numbers, that is, they give attention to the procedural contents in a traditional view of pre-requisites. It is discussed the formative deficiencies, for the initial and continuous, from the detected deficiencies.